2014
DOI: 10.2147/ijn.s53299
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord mesenchymal stem cells labeled with multimodal iron oxide nanoparticles with fluorescent and magnetic properties: application for in vivo cell tracking

Abstract: Here we describe multimodal iron oxide nanoparticles conjugated to Rhodamine-B (MION-Rh), their stability in culture medium, and subsequent validation of an in vitro protocol to label mesenchymal stem cells from umbilical cord blood (UC-MSC) with MION-Rh. These cells showed robust labeling in vitro without impairment of their functional properties, the viability of which were evaluated by proliferation kinetic and ultrastructural analyzes. Thus, labeled cells were infused into striatum of adult male rats of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Our group provided evidence, in previous studies, that a low nanoparticle concentration in the labeling process was enough to detect stem cell migration homing and tracking. Additionally, nanoparticle sizes of between 35 and 200 nm used in our previous studies showed magnetic characteristics adequate for detection by MRI [65][66][67]. This review corroborates the nanoparticle size findings among the selected studies (60 to 180 nm).…”
Section: Discussionsupporting
confidence: 85%
“…Our group provided evidence, in previous studies, that a low nanoparticle concentration in the labeling process was enough to detect stem cell migration homing and tracking. Additionally, nanoparticle sizes of between 35 and 200 nm used in our previous studies showed magnetic characteristics adequate for detection by MRI [65][66][67]. This review corroborates the nanoparticle size findings among the selected studies (60 to 180 nm).…”
Section: Discussionsupporting
confidence: 85%
“…MSCs can be isolated from the umbilical cord (UC) lining, subendothelial layer, perivascular zone, and the Wharton’s Jelly (WJ) (the gelatinous matrix in the umbilical cord that provides insulation and protection of the vein and arteries of the umbilical cord) [5] (Figure 1). The MSCs found in these regions of the hUC are multipotent and can differentiate into adipogenic, osteogenic, chondrogenic, and neuronal cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the stability of nanoparticles in the labeling process, previous studies by our group [90][91][92] evaluated SPION stability before labeling in different media and demonstrated that supplementation with 10% fetal bovine serum (FBS) contributed stabilized SPIONs in the culture medium during the labeling process [90,91,93]. This type of strategy was also reported in other studies [54,58,59,85,87], with FBS concentrations ranging from 5% to 20% during the labeling process of granulocytes or leucocytes with SPIONs.…”
Section: Discussionmentioning
confidence: 56%